Better Late Than Never: The Case of Manufacturing Company - Che Pak, Nur Azliani Haniza; Hussin, Muhammad Rosni Amir; Abdul Mutalib, Hafizah; Sulaiman, Aryati Juliana (2022)
The teaching case is about the costing practice in a furniture manufacturing company, Prima Bersatu Unggul Sdn. Bhd.(PBU). PBU is a well known company located in northern Malaysia, who always win the tender especially from Malaysian government. However, the CEO always confused when it comes to the profit of the company. Although they have secured many tender, but the company’s profit are still low. This situation has urged the CEO to appoint one of her staff to investigate further on costing process at PBU. The information provided in the case intends to test students understanding on the job order costing method and its application in a furniture manufacturing company. Furthermore, the case will also test the ability of students in determining the cost of a job in job-order costing. The concept for this teaching case is on job order costing and cost assignment process. The case is a decision case, in the field of Management Accounting.